(untitled) (Dhaka University Journal of Biological Sciences, 2022)
A pot experiment was conducted to evaluate the effects of organic manures and inorganic fertilizers on the growth and yield of red capsicum (Capsicum annuum L.). It was conducted on rooftop of a building in Bogura town, Bogura. The experiment consisted of twelve treatments with three replications and was laid out in Randomized Complete Block Design (RCBD). Treatments were T1: Control (-OM and -NPK), T2: 4 ton Nafco ha-1 + N23P10K25 kgha-1, T3: 4 ton ACI ha-1 + N23P10K25 kgha-1, T4: 4 ton Trichocompost ha-1 + N23P10K25 kgha-1, T5: 4 ton Kazi Farms ha-1 + N23P10K25 kgha-1, T6: 4 ton Mimpex ha-1 + N23P10K25 kgha-1, T7: 4 ton Mazim ha-1 + N23P10K25 kgha-1, T8: 4 ton McDonald ha-1 + N23P10K25 kgha-1, T9: 4 ton Paragon ha-1 + N23P10K25 kgha-1, T10: 4 ton Kazi Agro ha-1 + N23P10K25 kgha-1, T11: 4 ton Vermicompost ha-1 + N23P10K25 kgha-1 and T12:N46P20K50 kgha-1. Highest plant height (33.81 cm), leaf area (87.22 cm2 plant-1), number of leaves (43 plant-1), number of branches (6 plant-1), number of fruits (11 plant-1), fresh weight (0.60 g plant-1) and dry weight (12.67 g plant-1) were observed in treatment T4: 4 ton Trichocompost ha-1 + N23P10K25 kgha-1. Highest girth (3.18 cm) was observed in treatment T7: 4 ton Mazim ha-1 + N23P10K25 kgha-1. The overall best growth performance was achieved in T4: 4 ton Trichocompost ha-1 + N23P10K25 kgha-1 treatment. Dhaka Univ. J. Biol. Sci. 31(1): 9-18, 2022 (January)